2019
DOI: 10.1159/000500183
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Considerations in Physician-Assisted Death for Probable Alzheimer’s Disease: Decision-Making Capacity, Anosognosia, and Suffering

Abstract: Background: Requests for physician-assisted death (PAD) in patients with cognitive impairment are complex and require careful consideration. Of particular difficulty is determination of whether the request is voluntary and well considered. Results: Euthanasia and physician-assisted suicide (PAS) are both legal in The Netherlands, Luxemburg, Colombia, and Canada. Euthanasia is legal in Belgium, while PAS is legal in Switzerland and Oregon, Washington, Montana, Vermont, and California (USA). Upon a PAD request, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Arguments to support these statements include respect for the patient's autonomy, dignity, and quality of life. 11,18 GPs in this study also mention that the option for euthanasia in the late stage of dementia raises feelings of reassurance and relief in patients and relatives. On the other hand, GPs fear the influence of relatives at the decisive moment of euthanasia.…”
Section: Strengths and Limitationsmentioning
confidence: 77%
See 1 more Smart Citation
“…Arguments to support these statements include respect for the patient's autonomy, dignity, and quality of life. 11,18 GPs in this study also mention that the option for euthanasia in the late stage of dementia raises feelings of reassurance and relief in patients and relatives. On the other hand, GPs fear the influence of relatives at the decisive moment of euthanasia.…”
Section: Strengths and Limitationsmentioning
confidence: 77%
“…This argument emphasises the importance doctors assign to the autonomy of a patient and to sharing the decision process. 5,6,18 Hence, this is also an expression of the conflict between meeting the right of self-determination of the patient and the duty of a doctor to guarantee the quality of the care process at the end of life.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…Therefore, MAiD-NT is extremely dangerous, especially when extended to minors and people with psychiatric disorders, as well as in those whose cognitive impairments (e.g. dementia) make it difficult to assess decisional capacity [11,12]. The risk is that society could have the right to get rid of people with problems that require considerable resources, hypocritically masking it as a humanitarian act to be performed for the patient's own good [13][14][15][16].…”
Section: The Moral Debate About Maid-nt In Psychiatry and Unsolved Pr...mentioning
confidence: 99%
“…A recent review of attitudes and practices associated with euthanasia and PAS has found this to still be the case, with 70% of cases involving patients with advanced cancer (Emanuel et al, 2016). However, in more recent times, there have been appeals to extend this practice to patients with other diagnoses, including dementia (Mondragón et al, 2019) and chronic depression or chronic pain disorders (Dees et al, 2011). In the case of dementia, arguments in favour of PAS generally center on five broad themes Jakhar et al, 2020):…”
Section: Introductionmentioning
confidence: 99%
“…A recent review of attitudes and practices associated with euthanasia and PAS has found this to still be the case, with 70% of cases involving patients with advanced cancer ( Emanuel et al, 2016 ). However, in more recent times, there have been appeals to extend this practice to patients with other diagnoses, including dementia ( Mondragón et al, 2019 ) and chronic depression or chronic pain disorders ( Dees et al, 2011 ). In the case of dementia, arguments in favour of PAS generally center on five broad themes ( Tomlinson et al, 2015 ; Jakhar et al, 2020 ): • The economic burden posed by dementia, both at the level of individual caregivers and for society in general • The burden faced by caregivers in terms of stress, depression, time and effort needed to perform activities of daily living for the patient, and family conflicts • The distressing behavioural and psychological symptoms of dementia (BPSD) exhibited by several patients with these disorders, which often do not respond adequately to existing treatments.…”
Section: Introductionmentioning
confidence: 99%